2022
DOI: 10.1159/000520160
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 Lockdown on Food Ordering Patterns among Youths in China: The COVID-19 Impact on Lifestyle Change Survey

Abstract: <b><i>Introduction:</i></b> Limited studies have focused on how the COVID-19 outbreak and thereby lockdown had affected the youth’s food ordering patterns, which was associated with their dietary behaviors and could have longer term impacts on their later-life health status if the trend persists. This study aimed to evaluate changes in food ordering patterns among youths in China after the COVID-19 outbreak. <b><i>Methods:</i></b> The data were obtained from a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This study was based on the COVID-19 Impact on Lifestyle Change Survey (COINLICS), a national retrospective survey distributed via social media platforms in early May 2020 using a snowball sampling method. [4][5][6][7] More than 10000 youth participants at three educational levels (high school, college, and graduate school) in China have voluntarily reported their basic socio-demographic information and routine lifestyles in the months before (December 23, 2019 to January 23, 2020), during (January 24 to February 23, 2020), and after the COVID-19 lockdown (April 8 to May 8, 2020). The study was approved by the Sichuan University Medical Ethical Review Board (KS2020414).…”
Section: Methodsmentioning
confidence: 99%
“…This study was based on the COVID-19 Impact on Lifestyle Change Survey (COINLICS), a national retrospective survey distributed via social media platforms in early May 2020 using a snowball sampling method. [4][5][6][7] More than 10000 youth participants at three educational levels (high school, college, and graduate school) in China have voluntarily reported their basic socio-demographic information and routine lifestyles in the months before (December 23, 2019 to January 23, 2020), during (January 24 to February 23, 2020), and after the COVID-19 lockdown (April 8 to May 8, 2020). The study was approved by the Sichuan University Medical Ethical Review Board (KS2020414).…”
Section: Methodsmentioning
confidence: 99%
“…The outbreak of COVID-19 may further accelerate Internet use and its related problems in children and adolescents (11)(12)(13)(14). In January 2020, the Ministry of Education of China issued notices to postpone the opening of spring semester of all primary and secondary schools, and required students to stay at home and study through the Internet, which lasted for more than 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…Higher intakes of processed foods, refined grains, and sugar‐sweetened beverages negate lower intakes of minimally processed foods, and this has been observed in the literature 101 . Moreover, a study revealed that youth in China were ordering spicy hot pot meals, fried foods or hamburgers, and cakes/pastries the most via meal delivery applications during COVID‐19 102 . This again highlights that while there is a great potential for healthy choices to be made through online food retail platforms, there is a greater propensity towards unhealthier choices.…”
Section: Discussionmentioning
confidence: 88%
“…101 Moreover, a study revealed that youth in China were ordering spicy hot pot meals, fried foods or hamburgers, and cakes/pastries the most via meal delivery applications during COVID-19. 102 This again highlights that while there is a great potential for healthy choices to be made through online food retail platforms, there is a greater propensity towards unhealthier choices.…”
Section: Discussionmentioning
confidence: 99%